Pengaruh konsentrasi ekstrak daun mimba dan biji pinang terhadap mortalitas keong mas (Pomacea canaliculata L.) - Ma'wa, Niswatul; Hoesain, Mohammad (Jurnal Proteksi Tanaman Tropis, 2020)
The golden Apple Snail is one of the rice pest that damaging by shredding the leaves of young plant. The common control has some negative impacts on the environment, so that the application of phyto-moluscides becomes a solution forming environmentally friendly agriculture. Neem and areca nut are one of the raw materials that can be used to control golden apple snails. This study aims to determine the effect of the concentration of neem and areca leaf extracts so the result of the study can be information and recomendations for controlling golden apple snail. This study uses a factorial Completely Randomized Design method, the first factor is extract raw material consisting of neem leaf, areca nut, and combination, while the second factor is consentration 0.25 g/L, 0.50 g/L, 0.75 g/L and control, each treatment gets 3 replications. Extract was applied by direct aplication method. Observations are carried out every 12 hours for 96 hours after aplication. The observed variable is behavior change, inhibition of eating activity and golden snail mortality. Data was analyzed by ANOVA then continued whit Duncan’s advanced test. Based on the result on the parameters that have been tested, raw materials and concentration have the effect of changing behavior from the start of the aplication, inhibition of eating activity, even an increase in mortality of up to 100% in the treatment of areca extract and combination application.